The Museum of Visual Science and Optometry - Fisher, Edward J; Johnson, Catherine R (Canadian Journal of Optometry, 1981)
The Museum of Visual Science and Optometry is located in the Optometry building on the campus of the University of Waterloo. It forms part of the Waterloo Heritage Collections Association which also includes the Biology and Earth Sciences Museum and the Museum and Archive of Games. Administratively, this organization is separate from the University, but is closely related to it. The Museum of Visual Science and Optometry has its own board of consultants, consisting of several optometrists representing a cross section of the profession and its organizations.